The Role of Self-Esteem in Improving the Resilience of Juvenile Offenders - Sarah Syifanita; Naomi Soetikno (Philanthropy: Journal of Psychology)
Adolescents between the ages of 14 and 18 who commit crimes so that they must take responsibility for their actions by undergoing guidance at the Lembaga Pembinaan Khusus Anak (LPKA) are called juvenile offender. Juvenile offenders, who are adolescents in their developmental period, certainly experience pressures caused by various changes in environmental conditions that they must face while serving a sentence in the LPKA. Therefore, a juvenile offender must have resilience. This study aims to examine whether there is an influence between self-esteem and resilience in foster children in LPKA. The participants of this study were 132 juvenile offenders consisting of 64 juvenile offenders of LPKA X and 68 juvenile offenders of LPKA Y. The research data were collected by distributing questionnaires of Rosenberg Self-Esteem Scale (RSES) and Resilience Quotient (RQ) measuring instruments. The hypotheses were tested using the simple linear regression method. The test results show that self-esteem positively and significantly influences foster children's resilience in LPKA by 20.2%, p = 0.00 <0.05. Keywords: Self-esteem; Resilience; Juvenile offenders